THE LEGAL BENEFITS OF PLEA BARGAINING - Humberto Dalla; Paulo Wunder (Revista Eletrônica de Direito Processual, 2018)
The aim of this work is to present the historical evolution and legal nature of plea-bargaining in Brazil, then to analyze each of its benefits expressly provided for in the law of criminal organizations, including benchmarking between their characteristics and requirements. The article also takes care of the difference between the content to be analyzed by the judge in the approval decision of the agreement, depending on the type of negotiated benefit.